Solidification of heavy metals and PCDD/Fs from municipal solid waste incineration fly ash by the polymerization of calcium carbonate oligomers. (February 2022) - Lin, Xiaoqing; Chen, Jie; Xu, Shuaixi; Mao, Tieying; Liu, Weiping; Wu, Jiezhen; Li, Xiaodong; Yan, Jianhua
Abstract: Calcium carbonate oligomers are gel-state precursors that can be crystallized by low-temperature heat treatments to form an inorganic material with a monolithic and continuous structure, this material can effectively solidify/stabilize heavy metals in municipal solid waste incineration fly ash (MSWI FA). Calcium chloride addition achieves FA stabilization/solidification by the formation and polymerization of calcium carbonate oligomers. The effects of calcium, triethylamine (TEA), and water-washing pretreatment on the solidification of heavy metals by the polymer were studied. Consequently, as more calcium was added, the solidification improved. When the ratio of TEA/Ca 2+ was increased from 2:1 to 3:1, the solidification efficiency of As and Cd increased, but it decreased when the ratio was continuously increased to 4:1. After the water-washing pre-treatment, the MSWI FA had a significantly improved solidification effect on the heavy metals, and the solidification efficiencies of zinc, copper, cadmium, chromium, lead, and arsenic were 81.9%, 90.0%, 93.5%, 91.8%, 99.6% and 95.5%, respectively. Additionally, the solidification efficiency of PCDD/Fs was 56.5%. The heavy metals and PCDD/Fs in MSWI FA solidified by physical adsorption, wrapping and chemical precipitation. The continuous calcium carbonate structure adsorbed and encased the MSWI FA, and the heavy metals in the MSWI FA were converted from a free state to carbonate precipitates through carbonation, and the carbonate precipitate was more likely to be physical solidification by calcium carbonate. Graphical abstract: Image 1 Highlights: An innovative method of CaCO3 oligomer polymerization was used to solidify MSWI FA. Calcium carbonate fixes carbonated heavy metals by adsorption and wrapping. The coordinated solidification of PCDD/Fs was realized.